Measurements of Gamow-Teller strength in medium mass nuclei using (p,n) reactions at intermediate energies - Steyn, Douw (Department of Physics, 2023)
The simplicity of the beta decay process makes it a powerful tool for the investigation of the weak interaction and of nuclear structure. The two main operators involved, the Fermi (F) and Gamow-Teller (GT) operators, change just the isospin projection, and the isospin and spin projections of a nucleon respectively. Beta decay studies enable the extraction of the transition matrix elements to high precision. However, most GT transition rates deduced from beta decay measurements turn out to be smaller than the calculated single particle rates [1, 2, 3], a phenomenon that has become known as the quenching of GT strength. Beta decay studies are limited io radioactive nuclei in which the transitions are energetically possible. These are invariably between states of low excitation energy, and are also often relatively weak transitions. In addition, the calculation of the beta decay strengths is model-dependent. The model-dependence and uncertainties would be reduced if larger fractions of the total strength were analysed [4]. It is, however, possible to do so with the use of other probes of spin-isospin strength and to compare the results of these to those of beta decay. One such probe is the zero degree (p,n) reaction at intermediate energies [2, 5, 6]. Such a reaction is not subject to some of the limitations of beta decay in that any desired target nucleus may be probed and that the GT strength function may be investigated up to high excitation energies in the final nucleus. The essential similarity of the transition matrix elements of the two processes allows the measured (p,n) strengths to be converted to beta decay strengths.